A cysteine-rich extracellular protein, LAT52, interacts with the extracellular domain of the pollen receptor kinase LePRK2 - Tang, Weihua (2002)
Pollen germination and pollen tube growth are thought to require extracellular cues, but how these cues are perceived and transduced remains largely unknown. Pollen receptor kinases are plausible candidates for this role; they might bind extracellular ligands and thereby mediate cytoplasmic events required for pollen germination and pollen tube growth. To search for pollen-expressed ligands for pollen receptor kinases, we used the extracellular domains of three pollen-specific receptor kinases of tomato (LePRK1, LePRK2, and LePRK3) as baits in a yeast two-hybrid screen. We identified numerous secreted or plasma membrane-bound candidate ligands. One of these, the Cys-rich protein LAT52, was known to be essential during pollen hydration and pollen tube growth. We used in vivo coimmunoprecipitation to demonstrate that LAT52 was capable of forming a complex with LePRK2 in pollen and to show that the extracellular domain of LePRK2 was sufficient for the interaction. Soluble LAT52 can exist in differently sized forms, but only the larger form can interact with LePRK2. We propose that LAT52 might be a ligand for LePRK2.